Modeling “Wrong Side” Failures Caused by Geomagnetically Induced Currents in Electrified Railway Signaling Systems in the UK - C. J. Patterson; J. A. Wild; D. H. Boteler (Space Weather)
Abstract The majority of studies into space weather impacts on ground‐based systems focus on power supply networks and oil and gas pipelines. The effects on railway signaling infrastructure remain a sparsely covered aspect even though these systems are known to have experienced adverse effects in the past as a result of geomagnetic activity. This study extends recent modeling of geomagnetic effects on DC signaling for AC‐electrified railways in the UK that analyzed “right side” failures in which green signals are turned to red. The extended model reported here allows the study of “wrong side” failures where red signals are turned green: a failure mode that is potentially more dangerous. Railway lines using track circuit signaling, like those modeled in this study, are separated into a number of individual blocks. This study shows that a relay is most susceptible to “wrong side” failure when a train is at the end of a track circuit block. Assuming that each train is positioned at the end of the block it is occupying, the results show that the geoelectric field threshold at which “wrong side” failures can occur is lower than for “right side” failures. This misoperation field level occurs on a timescale of once every 10 or 20 years. We also show that the estimated electric field caused by a 1‐in‐100 years event could cause a significant number of “wrong side” failures at multiple points along the railway lines studied, although this depends on the number of trains on the line at that time.